Mesenchymal Wnt/β-catenin signaling induces Wnt and BMP antagonists in dental epithelium. (3rd April 2019) - Chen, Xiaoyan; Liu, Jing; Li, Nan; Wang, Yu; Zhou, Nan; Zhu, Lei; Shi, Yiding; Wu, Yingzhang; Xiao, Jing; Liu, Chao
ABSTRACT: Previous studies indicated that the elevated mesenchymal Wnt/β-catenin signaling deprived dental mesenchyme of odontogenic fate. By utilizing ex vivo or pharmacological approaches, Wnt/β-catenin signaling in the developing dental mesenchyme was suggested to suppress the odontogenic fate by disrupting the balance between Axin2 and Runx2. In our study, the Osr2-cre KI ; Ctnnb1 ex3f mouse was used to explore how mesenchymal Wnt/β-catenin signaling suppressed the odontogenic fate in vivo . We found that all of the incisor and half of the molar germs of Osr2-cre KI ; Ctnnb1 ex3f mice started to regress at E14.5 and almost disappeared at birth. The expression of Fgf3 and Msx1 was dramatically down-regulated in the E14.5 Osr2-cre KI ; Ctnnb1 ex3f incisor and molar mesenchyme, while Runx2 transcription was only diminished in incisor mesenchyme. Intriguingly, in the E14.5 Osr2-cre KI ; Ctnnb1 ex3f incisor epithelium, the expression of Noggin was activated, while Shh was abrogated. Similarly, the Wnt and BMP antagonists, Ectodin and Noggin were also ectopically activated in the E14.5 Osr2-cre KI ; Ctnnb1 ex3f molar epithelium. Recombination of E13.5 Osr2-cre KI ; Ctnnb1 ex3f molar mesenchyme with E10.5 and E13.5 WT dental epithelia failed to develop tooth. Taken together, the mesenchymal Wnt/β-catenin signaling resulted in the loss of odontogenic fate in vivo not only by directly suppressing odontogenic genes expression but also by inducing Wnt and BMP antagonists in dental epithelium.